Promoting malayan emergency state by using gaming platform as an illustrative medium / Mohammad Nor Anwar Hussin - Anwar Hussin, Mohammad Nor (2021)
Based on a series of events that took place in 2019 that seemed to elevate the Malayan communists as freedom fighters, rather than terrorists. If the narrative were to succeed, it would mean that the services of soldiers and security forces fighting day and night would be forgotten (Prof Dr. Zainur Rashid Zainuddin, 2020). Previous research shows that this issue arises because people already forgot the history of our nation. This was also proven from our survey research and findings. To strengthen the memory, we develop a game design which focuses on events happened during Malayan emergency 1948 -1960. This research is about using a gaming platform as an illustrative medium to promote the Malayan emergency state. Hence, the design objective is to remind the young generation to be discreet and vigilant towards the ideologies of communist.